2021
DOI: 10.3390/s21113792
|View full text |Cite
|
Sign up to set email alerts
|

The Protraction and Retraction Angles of Horse Limbs: An Estimation during Trotting Using Inertial Sensors

Abstract: The protraction and retraction angles of horse limbs are important in the analysis of horse locomotion. This study explored two methods from an IMU positioned on the canon bone of eight horses to estimate these angles. Each method was based on a hypothesis in order to define the moment corresponding with the verticality of the canon bone: (i) the canon bone is in a vertical position at 50% of the stance phase or (ii) the verticality of the canon bone corresponds with the moment when the horse’s withers reach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…IMUs have been used effectively in the field to characterize anomalies in horse locomotion since they offer a non-invasive wearable measurement of locomotor indicators. These sensors have been proposed as an aid for lameness detection [15][16][17], for gait classification [18], for horse speed estimation [19], for evaluation of the effect of shoes on break over [20], or for the evaluation of different rehabilitation methods [20]. They also offer an alternative to traditional systems such as optoelectronic systems to identify the phases of locomotion [21][22][23][24][25] or estimate the horse's protraction and retraction angles [16].…”
Section: Introductionmentioning
confidence: 99%
“…IMUs have been used effectively in the field to characterize anomalies in horse locomotion since they offer a non-invasive wearable measurement of locomotor indicators. These sensors have been proposed as an aid for lameness detection [15][16][17], for gait classification [18], for horse speed estimation [19], for evaluation of the effect of shoes on break over [20], or for the evaluation of different rehabilitation methods [20]. They also offer an alternative to traditional systems such as optoelectronic systems to identify the phases of locomotion [21][22][23][24][25] or estimate the horse's protraction and retraction angles [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stance and stride duration measurements had a higher precision [ 56 ]. As opposed to OMC, these angular velocity methods were also able to accurately estimate protraction and retraction angles of horse limbs [ 57 ].…”
Section: Locomotor Analysis In Sound Horses Using Imusmentioning
confidence: 99%
“…Many studies have demonstrated that inertial measurement units (IMUs) are a real alternative to motion capture systems [ 17 ]. The use of IMUs allows the recording of the horse’s locomotion with onboard technologies and in field conditions [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Stance-phase detection methods from IMUs mounted on canon bones [ 18 , 21 , 22 ], pasterns [ 22 ], and hooves [ 22 , 23 , 24 ] have been recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…Stance-phase detection methods from IMUs mounted on canon bones [ 18 , 21 , 22 ], pasterns [ 22 ], and hooves [ 22 , 23 , 24 ] have been recently developed. IMUs also allow the measuring of protraction and retraction angles [ 19 ]. Some studies also developed asymmetry quantification methods to assist with veterinarian examinations [ 20 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%